PENGEMBANGAN BAHAN AJAR MENULIS RINGKASAN DAN IKHTISAR PADA MATA KULIAH PENGEMBANGAN KETERAMPILAN MENULIS FKIP UNIVERSITAS BATURAJA - Muhamad Doni Sanjaya; Muhamad Rama Sanjaya (Jurnal Educative: Journal of Educational Studies, 2018)
This study aims to (1) describe the need for text book in writing learning that’s become as the development of instructional material, (2) produce textbooks that fit the needs analysis of students, (3) describes the potential effects of textbook summaries and overviews of learning outcomes. This study is a research and development. Subjects in this study were students of Language, Literature Indonesian and Regional, the Faculty of Teacher Training and Education, University of Baturaja. The results show that Summary Writing and Summary textbooks of these development outcomes have a potential influence in improving students' ability and understanding of writing materials. Keywords: development, textbooks, writing, teaching materials.